2008
DOI: 10.1094/ats-2008-0118-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Sod Production Utilizing an Improved Seeded Bermudagrass Cultivar

Abstract: Improved, seeded bermudagrass (Cynodon spp.) cultivars have the potential to be used for sod production, but there has been no research to determine appropriate methods for this application. The objective of this study was to determine the effects of sod netting and the growth regulator, trinexapac‐ethyl (TE), on the time required to harvest sod using a seeded bermudagrass. The experimental design of this study was a strip‐plot with sod netting being the whole plot treatment and TE treatments (0.059 lb ai/acre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Weed Table 1. Long-term mo.ly average air temperature and precipitation from weather stations located in close proximity to the field sites in Somma Lombardo (2000-10), Sommacampagna (1993-2008), and Legnaro (1963-2007 control ratings of different species were combined to form unique values based on plant size, discoloration or necrosis, and general plant vigor (Main et al, 2004). Immediately after weed control estimations, plots were handweeded to avoid weed interference on assessments of turf regrowth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weed Table 1. Long-term mo.ly average air temperature and precipitation from weather stations located in close proximity to the field sites in Somma Lombardo (2000-10), Sommacampagna (1993-2008), and Legnaro (1963-2007 control ratings of different species were combined to form unique values based on plant size, discoloration or necrosis, and general plant vigor (Main et al, 2004). Immediately after weed control estimations, plots were handweeded to avoid weed interference on assessments of turf regrowth.…”
Section: Methodsmentioning
confidence: 99%
“…The primary concern of sod producers is to obtain an adequate quality for harvest in the shortest possible period with minimal inputs. However, the time necessary to obtain a sod ready for harvest depends on grass species, cultivar, environmental conditions, and cultural practices (Beard, 1973;McCalla et al, 2008). Highquality sod is expected to have full green color, no weeds, in addition to high density and uniformity, and other technical traits, such as strength for transplanting (McCalla et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, bermudagrass, like several other turfgrass species, can be established not only from seed but also from sprigs, plugs, or sod. In the southern United States, bermudagrass is mostly propagated by sod (McCalla et al, 2008). In a 1‐yr study, Maurer (2007) successfully established bermudagrass from sod using SDI in combination with a sprinkler system to keep the soil surface moist.…”
mentioning
confidence: 99%
“…Several devices have been designed to quantitatively measure sod shear strength (Burns and Futral, 1980;Goatley et al, 1997;Parish, 1995;Rieke et al, 1968;Sharpe et al, 1989;Shildrick, 1982;Sorochan and Rogers, 2000). These devices, or modifications based on them, have constituted the majority of studies where sod strength has been reported (e.g., Agnew and Christians, 1992;Cutulle et al, 2013;Giese et al, 1997;Hall, 1980;Hall et al, 1985;Hall and Bingham, 1993;Hurley and Skogley, 1975;Li et al, 2011;McCalla et al, 2008;Rieke and Beard, 1969;Ruemmele et al, 2001;Shearman et al, 2001;Taylor and Schmidt, 1980). Although a quantitative measurement of sod strength can be made and related to specific treatment effects (e.g., N rate, growth regulators, species, and cultivar comparisons, etc.…”
mentioning
confidence: 99%